Turnout or turned off? Electoral participation in Dublin in the 21st century - Kavanagh, Adrian (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
Voter turnout is defined as the percentage number of registered voters who vote in an election - although the valid adult population (those aged 18. and over). is taken as the base from which turnout rates are calculated in other countries. such as the USA. Turnout levels have generally been in decline in Western democracies for the past few decades, as is also the case in the Republic of Ireland. TurnoUiS in socially-deprived urban areas have fallen to exceptionally low levels, particularly in innercity and western suburban areas in Dublin. Problems related to voter turnout feature amongst the most significant concerns facing the Irish political system at present. Democracy is weakened if the numbers voting in elections are in decline, while cross-constituency turnout variations involving socio-economic or demographics biases will have an impact on the final election results and resulting policy outcomes, which may act to further peripheralise an already marginalised groups. It is important to study how-economic and demographic factors may influence turnout levels.
Keywords: Urban geography -- Ireland